Tissue malondialdehyde and adenosine triphosphatase level after experimental liver ischaemia-reperfusion damage - Ilhan, N; Halifeoglu, I; Ozercan, HI; Ilhan, N (Wiley, 2001)
Functional irregularities due to damage after ischaemia-reperfusion vary depending upon the organs affected. High energy phosphates such as ATP and ADP are destroyed after ischaemia-reperfusion damage. Subsequently, protons and inorganic phosphates accumulate within the cells and the proton pumps such as adenosine triphosphatase (ATPase), which maintain intracellular ion balance are damaged, In the present study, malondialdehyde (MDA), a product of lipid peroxidation, was measured as an indicator of tissue damage. Additionally, we measured sodium-potasium-ATPase levels and determined the interactions between MDA and Na+-K+ ATPase levels. A total of 31 female guinea pigs were divided into four groups: sham operated guinea pigs (group 1), ischaemia-reperfusion (group 2), ischaemia-reperfusion + superoxide dismutase (SOD) (group 3), ischaemia-reperfusion + allopurinol (group 4). Following reperfusion, the livers of guinea pigs in each group were removed for histopathological examination and the levels of MDA and Na+-K+ ATPase were determined in homogenized tissue samples. There was a statistically significant (p < 0.05) reduction in tissue MDA levels in group 2 when compared with group 1. The level of tissue MDA in groups 3 and 4 was significantly lower than tissue NMA levels of group 2. However, there was a statistically significant (p < 0.05) reduction in tissue Na+-K+ ATPase levels of group 2 when compared with group 1. Similiarly, the level of tissue Na+-K+ ATPase in groups 3 and 4 was significantly higher than the tissue Na+-K+ ATPase levels of group 2. The results of the histopathologic examination also revealed the beneficial effects of the use of SOD and allopurinol in preventing liver damage in cases of ischaemia-reperfusion. Although the levels of MDA and Na+-K+ ATP ase in group 2 were not equal to the level in group 1, antioxidant therapy significantly improved the tendency to reverse the effects of ischaemia-reperfusion and to protect the liver from damage due to ischaemia-reperfusion. Copyright (C) 2001 John Wiley & Sons, Ltd.
Keywords: MDA; Na+-K+ ATP ase; ischaemia-reperfusion